Effect of corncob powder concentration on properties of inlay waxes - Irnawati, Dyah; Harsini; Widjijono; Siswomihardjo, Widowati; Sunarintyas, Siti; Yasnawi, Mohammad Imanuddin; Verani, Dhea Maurilla (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Corncob powder is a promising filler that needs to be assessed when it is incorporated into inlay waxes to modified its properties. Purpose: This study aims to investigate the effect of different concentrations of corncob powder filler on physical and mechanical properties of inlay waxes. Methods: Five groups of inlay waxes were prepared from paraffin, corncob powder, carnauba wax, and beeswax in varying proportions (w/w%), namely, group I (70:0:25:5), II (65:5:25:5), III (60:10:25: 5), IV (55:15:25:5), and V (50:20:25:5). The wax mixture was heated at 80°C, filtered, added with corncob powder, and stirred until homogeneous then poured into mold for melting point, residue on ignition, flow, hardness, and trimming samples. They were based on ANSI/ADA specification no.122 and ASTM D 1321. The data were analyzed through one-way ANOVA, post-hoc LSD, and Tamhane tests (p = 0.05), except trimming test data. Results: One-way ANOVA revealed that the concentration of corncob filler influenced all inlay waxes properties (p<0.05). LSD and Tamhane post-hoc test, showed significant different among mostly between groups of tests. Addition corncob powder increased the melting point, hardness, and residue of inlay waxes but decreased the flow of inlay waxes. Addition corncob did not influence the trimming property of inlay waxes. Conclusion: The concentration of corncob filler added in inlay wax compositions influenced the melting point, flow, hardness and residue properties but did not influence trimming properties. Inlay wax containing 10% corncob filler potential as a local inlay wax, but further research should be done to overcome the residue on ignition property that higher than standards.